Collaborative development on a digital learning platform: The potential of AI tools for facilitation - Kurki, Anna-Leena; Koskela, Inka; Yli-Kaitala, Kirsi (Human Technology, 2024)
Digital learning platforms featuring artificial intelligence (AI)-based tools are being increasingly used at workplaces. This study investigated the opportunities that AI tools offer for facilitating the collaborative development of work on a learning platform called Howspace. The data comprised interviews with platform developers (n=4) and facilitators (n=10). Content analysis explored the interviewees’ conceptions of the use of AI tools in collaborative development. It identified four AI tool functions—task assistant, participant assistant, process assistant, and interaction assistant—along with their associated benefits and limitations. Platform developers saw more opportunities for the use of AI tools, whereas the facilitators saw more challenges. These challenges were primarily related to the facilitators’ limited understanding of the algorithms’ logic. The study proposes that enhancing the transparency of algorithms could improve the usability of AI tools. A better understanding of algorithmic operations could mitigate the identified challenges, and improve facilitators’ experience of employing AI tools.